USE OF DERMOGLANDULAR FLAP (BUROW’S TRIANGLE) AFTER NEOADJUVANCE IN UPPER QUADRANT TUMORS OF THE BREAST - Oliveira, Paula Stephanie Duarte; Silva, André Vallejo da; Pires, Douglas de Miranda; Hoffman, Tayra Dall’oglio; Alves, Luciana Jandre Boechat (Mastology, 2018)
Mastectomy has been, in the past, the first treatment of choice for locally advanced breast tumors, especially when the neoadjuvant response is partial, and the tumor’s location doesn’t allow an aesthetic outcome when using usual quadrantectomy. Oncoplastic techniques are good solutions for these tumors allowing to resect big areas, removing the whole tumor and preserving breast symmetry. This case describes a dermoglandular flap technique to be used in advanced upper quadrant tumors in post neoadjuvance patients.